(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1992)
On the basis of the results of former studies by the present authors five main groups of bears are recognized: Ursus gr. minimus - thibetanus (black bears), Ursus gr. etruscus (etruscan bears), Ursus gr. arctos (brown bears), Ursus gr. deningei - spelaeus (cave bears) and Ursus gr. maritimus (white bears). Black bears seem to have disappeared from Europe during the Late Pliocene, immigrated again at the beginning of the Middle Pleistocene, and definitively died out in Europe at the beginning of the Late Pleistocene. Etruscan bears occur more or less contemporaneously in the southern areas of Europe and Asia during the Late Pliocene. The Asian branch apparently became extinct at the end of this period, while the European stock survived, giving rise to more advanced representatives during the Early Pleistocene. Brown bears seem to have originated in Asia. This group dispersed widely in holoarctic areas diversifying into a great number of varieties. They reached Europe presumably at the very end of the Early Pleistocene. The arrival of brown bears in Europe is a crucial event, which approximately coincides with the great faunal turnover which marks the Early-Middle Pleistocene transition. Brown bears replaced the etruscan bears, typical of the Villafranchian faunal assemblages, and gave rise to the cave bear line. Cave bears were very successful in Europe during the Middle and Late Pleistocene and disappeared at the end of the last glaciation or even at the very beginning of the Holocene. White bears presumably originated from northern Eurasian brown bear populations during the Late Pleistocene.